PECULIARITIES OF DEVELOPMENT OF PEDAGOGICAL COMPETENCE OF STUDENTS (American Journal of Pedagogical and Educational Research, 2023)
This article presents the concept of competence and information about competence, specific features of the development of pedagogical competence of students.